IMPLEMENTASI METODE WEIGHTED AGGREGATED SUM PRODUCT ASSESMENT DALAM MENENTUKAN KEDELAI TERBAIK PRODUKSI TAHU, TEMPE - Anggraini, Inda; Arif, Alfis; Ningrum, Ichda Utami (JUSIM (Jurnal Sistem Informasi Musirawas), 2024)
This research aims to implement the Weighted Aggregated Sum Product Assessment method in identifying soybeans as raw materials in the production of tofu and tempeh. Tofu and tempeh production often experiences production failures, such as the tofu compaction process being insufficient or the texture being too dense, the tempeh fermentation process being less than optimal and so on. This is influenced by poor soybean raw materials, both in terms of texture and color and the selection of soybeans which is still done directly by looking at the color and brand. Meanwhile, these two things do not necessarily correspond to the right criteria for tofu and tempeh production. In this research, the Weighted Aggregated Sum Product Assessment method was used in making decisions to determine the best soybeans for producing tofu and tempeh based on 4 selection criteria, namely soy color, soy size, soy moisture and soy texture. All these criteria are then processed to obtain the best soybean results that are appropriate for the raw material for making tofu and tempe, namely soybeans from the Ahok supplier with a value of 4.475.